Illness-Perception, Coping Strategies and Psychological Distress among Polycystic Ovary Syndrome Women - Qurat-Ul-Ain, Afsheen Gul, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovary syndrome is the most common disorder among women. Globally 2.2% to 26 % of the women suffers from this syndrome. Illness perception change the coping strategies and attitude towards illness. Psychological distress is assumed to be significantly influenced by coping strategies and illness perception. Aim: The present study aimed to investigate the relationship among illness-perception, coping strategies and psychological distress among PCOS women. Methods: A sample of n=90 females with age range of 20 to 35 years (M= 26.3, SD=3.3). Through probability sampling strategy. Illness perception questionnaire (Broadbent et al., 2006), brief coping scale (Carver, 1997) and psychological distress scale (Kessler et al., 1992) measures were used. Findings: The results were analyzed through Pearson Product Moment Correlation and Multiple hierarchical regression tests which shows significant relationship among psychological distress and one dimension of brief coping (problem focused coping), whereas shows significant positive and negative relationship with illness perception dimensions Practical Implication & Conclusion: Findings implies that high psychological distress would be due to high perception of illness. Women uses problem focused coping strategies more readily cope the stress in illness and experienced less psychological distress in polycystic ovary syndrome. So this review helps the clinicians in reducing distress among PCOS women. Keywords: Illness perception, Coping Strategies, Psychological distress, polycystic ovary syndrome